“Development and psychometric study of the scale of the positive relationship PRIM+19 in peruvian university students“ - Vilca, Lindsey W. (2023)
“Background Positive relationships are one of the most important components within the PERMA model since they facilitate the development of the other components. However, in the scientific literature, few instruments have been identified with solid psychometric properties that measure positive relationships in university students and adequately represent the construct. Therefore, the study aims to develop and study the psychometric properties of the PRI+19 positive relationships scale through Confirmatory Factor Analysis, factorial invariance, and relationshipbased validity with other variables. Method A pilot sample of 201 university students (43.8% men and 56.2 women) between the ages of 18 and 34 (M=20.9; SD=2.74) was collected. The confirmatory sample consisted of 450 university students of both sexes (30.2% men and 69.8 women) between the ages of 18 and 35 years (M=21.9; SD=3.15). Along with the PRI+scale, other instruments were applied to measure satisfaction with life and psychological well-being. Results In the pilot study, the Exploratory Factor Analysis showed the presence of three factors that could explain 54.5% of the items. In the confirmatory study, the Confirmatory Factor Analysis showed that the model of three dimensions related to 19 items presents the best adjustment indexes compared to other models (χ2=541.61; df=149; CFI=0.97; TLI=0.97; RMSEA=0.077 [IC90% 0.070 ‒ 0.084]). The scale also showed evidence of being strictly invariant for the groups of men and women. Finally, it was shown that the development of the positive bonds dimension positively predicts psychological well-being (0.35) and life satisfaction (0.20). The positive relationship management dimension positively predicts psychological well-being (0.28) and life satisfaction (0.29). Similarly, the integration dimension positively predicts psychological well-being (0.48) and life satisfaction (0.52). Conclusion This study suggests that the PRIM+19 scale is a useful tool from which valid and reliable interpretations of positive relationships in Peruvian university students can be obtained.“